ITSM Strategy Using CSI on ITIL V.3 To Improve IT Services - Aeni, Khurotul; Adzin, Randi (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2020)
The SIMBARU (Academic information System) has The obstacles that currently occur in the SIMBARU process is how to utilize an IT-based academic service system that is ready to run/use in the optimal time optimally, providing services with the right target, fast access that can provide satisfaction to users (user), as well as vision of mission and institutional business objectives can be realized. By using PDCA data analysis Method (Plan, Do, Check, and ACT), it is expected to design a SIP document (Service Improvement Plan) to improve the performance of SIMBARU. The design of SIP documents on SIMBARU can be done by using IT Infrastructure Library V. 3 by analyzing the condition of SIMBARU which then produce output in the form of SIP. Results of this research SIP designed in accordance with the knowledge gained from the results of the analysis, can be used as a strategy to improve IT services in college, which resulted in recommendation of improvement and output in the form of SIP. Repair and SIP recommendations are expected to be implemented to improve IT services, so that the IT service i.e. SIMBARU can help the academic staff in conducting academics in college.